Annulment of Arbitral Awards under the Federal UAE Arbitration Law - AL ANI, ABDULLAH RIYADH RABEE (2019)
Federal Law number 6 of 2018 is the New UAE Arbitration law – it is composed of 61 articles that control the practice of arbitration in the UAE. The UAE Federal Arbitration Law sets out the grounds for annulment of arbitral awards under article 53 thereof. The grounds set out under article 53 – as well as other articles related to annulment – is analyzed to understand how the UAE courts might determine a challenge for the annulment of an arbitral award. This analysis is supplemented national and international court judgements dealing with arbitrations and arbitral awards. The grounds for annulment of an arbitral award are broken down in this paper into the following categories: invalidity in the arbitration agreement, constitution of the arbitral tribunal, conduct of the arbitral process, the form and content of an arbitral award, and for matters of arbitrability and public policy.